Prevalence of antibody seroconversion to Toxoplasma gondii in uveitis and non‐uveitis dogs. Issue 1 (3rd May 2019) - Kosec, Goran; Hacin, Biljana; Sansom, Philip G; Weaver, Gereth; Dewhurst, Emma; Carter, James W
Abstract : Objectives: To evaluate the prevalence of seroconversion to Toxoplasma gondii in dogs with uveitis and dogs without uveitis. Methods: In total, 135 dogs were evaluated: 51 dogs were diagnosed with uveitis, and 84 dogs were without uveitis. Latex agglutination tests were performed on all sera, and the results were evaluated. Results: Overall, 7.8 and 6.0 per cent of sera were positive for the presence of anti‐ T gondii antibodies (dilution ≥1:64) in the groups with uveitis and non‐uveitis dogs, respectively. The frequency distribution of variables (positive and negative results in the uveitis and the non‐uveitis group of dogs) was tested with Fisher's exact test. There was no statistically significant difference between groups (P=0.73). Clinical significance: These findings suggest that evidence of exposure to T gondii was not significantly different between uveitis and non‐uveitis groups of dogs and that the possible association between exposure to T gondii and canine uveitis requires further investigation. This study is the first to report the seroprevalence of anti‐ T gondii antibodies in dogs in the UK population and the first to report the seroprevalence of anti‐ T gondii antibodies in dogs with uveitis.